VLibras-BOX - Flexible Portuguese-LIBRAS Translation Server Encapsulation for Distributed, Centralized or Hybrid Scenarios - Grigório, Francielly; Júnior, Jaelson; Duarte, Alexandre; Costa, Rostand; Ramos, Daniel; Pessoa, Gutenberg (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2015: Proceedings of the 21st Brazilian Symposium on Multimedia and the Web, 2015)
In this paper we present the concept of a VLibras-Box, a building box for distributed sign-language translation infrastructures. A VLibras-Box encapsulates a Portuguese to Brazilian Sign Language translation service and additional components needed to combine multiple VLibras-Boxes in order to assembly a fault-tolerant and scalable translation infrastructure. We present three different application scenarios, hanging from a single VLibras-Box, where the translation endpoint is defined in an static way to multiple translation servers scenarios with dynamic selection and a two-way load balancing strategy to compose public, private and hybrid fault-tolerant distributed translation infrastructures.